Carta de Alfredo Margenat Marrero - Margenat Marrero, Alfredo; Todd, Roberto H. (My University, 1937)
Recuerdos del pasado.
Keywords: Margenat Marrero, Alfredo--Correspondence.; Margenat Marrero, Alfredo--Correspondencia.; Todd, Roberto H.--Correspondence.; Todd, Roberto H.--Correspondencia.